UPAYA MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DENGAN MENGGUNAKAN MODEL THINK-TALK-WRITE (TTW) DI SMP NEGERI 4 SIBOLGA - Theresia Meldaria Gulo (JURNAL MathEdu (Mathematic Education Journal), 2018)
This study aims to know whether there is an increase students’ mathematical communication ability by using Think Talk Write (TTW) learning model at the eighth grade students of SMP Negeri 4 Sibolga 2017/2018 Academic Year. The research was conducted by applying action research with 30 students as the subject. The research consisted two cycles and the end of each cycle was given a set of test. Based on descriptive analyzes, it could be found that a) The first cycle was found 22 students were completed (73.33%) through mathematical communication ability test and the second cycle was found 27 students were completed (90%), increase of 16.6% and b) the average of students’ mathematical communication ability in the first cycle was 70.41 (middle category) and in the second cycle was 81.45 (high category), increase of 11.04. It is concluded there is an increase students’ mathematical communication ability by using Think Talk Write (TTW) learning model at the eighth grade students of SMP Negeri 4 Sibolga 2017/2018 Academic Year.